Nothophytophthora gen. nov., a new sister genus of Phytophthora from natural and semi-natural ecosystems - Jung, T; Scanu, B; Bakonyi, J; Seress, D; Kovács, G M; Durán, A; von Stowasser, E Sanfuentes; Schena, L; Mosca, S; Thu, P Q; Nguyen, C M; Fajardo, S; et al. (Persoonia, 2017)
During various surveys of Phytophthora diversity in Europe, Chile and Vietnam slow growing oomycete isolates were obtained from rhizosphere soil samples and small streams in natural and planted forest stands. Phylogenetic analyses of sequences from the nuclear ITS, LSU, β-tubulin and HSP90 loci and the mitochondrial cox1 and NADH1 genes revealed they belong to six new species of a new genus, officially described here as Nothophytophthora gen. nov., which clustered as sister group to Phytophthora. Nothophytophthora species share numerous morphological characters with Phytophthora: persistent (all Nothophytophthora spp.) and caducous (N. caduca, N. chlamydospora, N. valdiviana, N. vietnamensis) sporangia with variable shapes, internal differentiation of zoospores and internal, nested and extended (N. caduca, N. chlamydospora) and external (all Nothophytophthora spp.) sporangial proliferation; smooth-walled oogonia with amphigynous (N. amphigynosa) and paragynous (N. amphigynosa, N. intricata, N. vietnamensis) attachment of the antheridia; chlamydospores (N. chlamydospora) and hyphal swellings. Main differing features of the new genus are the presence of a conspicuous, opaque plug inside the sporangiophore close to the base of most mature sporangia in all known Nothophytophthora species and intraspecific co-occurrence of caducity and non-papillate sporangia with internal nested and extended proliferation in several Nothophytophthora species. Comparisons of morphological structures of both genera allow hypotheses about the morphology and ecology of their common ancestor which are discussed. Production of caducous sporangia by N. caduca, N. chlamydospora and N. valdiviana from Valdivian rainforests and N. vietnamensis from a mountain forest in Vietnam suggests a partially aerial lifestyle as adaptation to these humid habitats. Presence of tree dieback in all forests from which Nothophytophthora spp. were recovered and partial sporangial caducity of several Nothophytophthora species indicate a pathogenic rather than a saprophytic lifestyle. Isolation tests from symptomatic plant tissues in these forests and pathogenicity tests are urgently required to clarify the lifestyle of the six Nothophytophthora species.
Keywords: evolution; phylogeny; Peronosporaceae; caducity; oomycetes; breeding system